2m-1=-6m+5

Add 6m to both sides of the equation.

2m-1+6m=5

Add 2m and 6m.

8m-1=5

8m-1=5

Add 1 to both sides of the equation.

8m=5+1

Add 5 and 1.

8m=6

8m=6

Divide each term in 8m=6 by 8.

8m8=68

Cancel the common factor of 8.

Cancel the common factor.

8m8=68

Divide m by 1.

m=68

m=68

Cancel the common factor of 6 and 8.

Factor 2 out of 6.

m=2(3)8

Cancel the common factors.

Factor 2 out of 8.

m=2⋅32⋅4

Cancel the common factor.

m=2⋅32⋅4

Rewrite the expression.

m=34

m=34

m=34

m=34

The result can be shown in multiple forms.

Exact Form:

m=34

Decimal Form:

m=0.75

Solve for m 2m-1=-6m+5